Pīrs and Politics in Punjab, 1937–2013. (12th January 2018) - MALIK, ADEEL; MALIK, TAHIR
Abstract: This article provides a first systematic mapping of politically influential shrines across Pakistani Punjab by identifying shrine-related families that have directly participated in elections since 1937. One of the earliest entrants in the politics of pre-partition Punjab, shrine elites ( pīrs ) have shown remarkable persistence in electoral politics post independence. We find striking long-run continuities in the initial configuration of religion, land, and politics fostered during colonial rule and embodied in political shrines. Exploring possible mechanisms of this persistence, we emphasize the role of shifting political alliances, repeated military interventions, marital ties among shrine elites, and preservation of political brokerage. Defined by their privileged 'origins and associations' and organized as a group with a strong sense of solidarity around protecting common interests, the pīrs are a key component of Punjab's power elite, the study of which is central to understanding the genesis and persistence of elites and institutions.